WHY ORGANIZATIONAL CHANGE IS HARD—AND HOW TO MAKE IT EASIER. Issue 105 (27th April 2022) - Andersen, Erika
Abstract: The author explains why organizational change can be such a difficult endeavor, and what leaders can do about it. And it is not just in business. She points out that this also happens in "charitable and religious organizations, academic institutions and government entities." As a species, humans have "anti‐change wiring, " yet in today's fast‐paced world "We need to re‐wire ourselves to be more comfortable with and open to change; we need to become more change‐capable." Based on research at the author's company, Proteus, a figure is presented, representing what she calls "The Change Arc." It outlines what happens from when a change is proposed to when it occurs, including the mindset shifts leading to new behaviors. For helping people embrace change, she proposes four "change levers, " which "are force multipliers that help accelerate people through their mindset shift around change."